Manejo pré-abate de bovinos - Quintal, Lais Spinola [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The pre-slaughter moment begins with the animal´s loading on the farm and ends up in its drain. It is a period in which the animal is under physical stress caused by hunger, thirst, fatigue, injuries, and extremes of temperature and psychological stress, due to restraint, handling, innovation and fear. Stress and inappropriate handling bring bad consequences for the final product´s quality, requiring better handling conditions, facilities and equipment. Examples of consequences of mishandling: meat with abnormal color, DFD meat (dark, firm and dry), reduced product´s shelf life, bruises and broken bones in carcasses. The operators should be trained and oriented on the basic principles of biology, behavior and management of cattle. At every step of the pre-slaughter moment, the animals should be handled calmly and quietly to avoid excitement and stress. Operators should avoid shouting, whistling or any noise since cattle have very sensitive ears and can become stressed. If the animals refuse to move, the cause of the problem should be determined

O período pré-abate se inicia no embarque do animal na propriedade e acaba na sua sangria. É um período em que o animal está submetido a estresse físico decorrente de fome, sede, fadiga, injúrias, extremos de temperatura e/ou a estresse psicológico devido a contenção, manejo, inovações e medo. O estresse e o mau manejo trazem conseqüências ruins para a qualidade do produto final, sendo necessárias melhores condições de manejo, instalações e equipamentos. São exemplos de consequências do manejo inadequado as carnes com colorações anormais, a carne DFD (dark, firm and dry), o produto com menor vida de prateleira, hematomas em carcaças e ossos quebrados. Os funcionários que lidam com os animais devem ser treinados e orientados sobre os princípios básicos de biologia, comportamento e manejo do gado. Em todas as etapas do período pré-abate os animais devem ser manejados calmamente e em silêncio para evitar agitação e estresse. Os operadores devem evitar gritos, assobios ou qualquer barulho, pois bovinos possuem ouvidos muito sensíveis e podem ficar estressados. Se os animais recusam-se a mover deve-se determinar a causa do problema
Keywords: Bovino de corte; Animais – Proteção; Animal welfare; Cattle